Digital divide and e-inclusion as challenges of the information society : research review - Zdjelar, Robertina (Array, 2021)
The issue of e-Inclusion has become an important topic and increasingly gains significance if one takes into account the global trend of digital transformation in the development of the information society and that the digital divide is still present. The reason more for taking the e-Inclusion of all social groups as a challenge has recently been the Covid-19 pandemic and natural disasters (earthquakes, floods) that change the norms of social behavior, require adaptation and create new rules. Users" ability to use digital services and goods as well as open data provided by public and private organizations which ultimately results in greater access to relevant information as well as improved quality of life and are a key factor for the effectiveness of digital transformation and the economic justification of investing in advanced digital technologies, goods and services. The digital divide manifests itself on certain social groups, which is a social problem. However, despite these initiatives, there are still limitations that prevent certain population groups from becoming e-inclusive members of the information society. This paper presents an overview of the analysis results of the research perspective in which scientific and professional papers consider the concepts of e-Inclusion and digital divide as a challenge. The multiperspectiveness and multidimensionality of the concept of e-Inclusion indicates its significant role in the development of the information society.